Microstructural evolution and stress state related to mechanical properties of electron beam melted Ti-6Al-4V alloy modified by laser shock peening. (1st August 2020) - Lan, Liang; Jin, Xinyuan; Gao, Shuang; He, Bo; Rong, Yonghua
Abstract: This work characterizes microstructural evolutions of electron beam melted (EBM) Ti-6Al-4V alloy modified via laser shock peening (LSP). The depth stress distribution and tensile properties of EBM Ti-6Al-4V alloy were measured before and after LSP. The results indicate that microstructure consists of β phase with 7.2% ± 0.4% vol.% and balance α lamellar in EBM sample, and the α lamella was refined into nano-equiaxed grains and submicro-equiaxed grains after LSP. The dominant refinement mechanism is revealed during LSP. Stacking faults were found in the LSP-treated sample, and their corresponding planes were determined as (0001) basal plane, (10 1 ¯ 0) prismatic plane, and (10 1 ¯ 1 ¯ ) pyramidal plane obtained by high resolution transmission electron microscopy. The subgrains and high-angle grains formed during dynamic recrystallization were identified by selected area electron diffraction pattern. The LSP treatment produces a significantly residual compressive stress approximately -380 MPa with the depth of compressive stress layer reaching 450 μm. Strength and elongation of the EBM sample were significantly increased after LSP. The strength and ductility enhancements are attributed to compressive stress, grain refinement and grain gradient distribution of α phase.